Pengaruh Gaya Kepemimpinan Situasional dan Kepuasan Kerja Terhadap Kinerja Karyawan: Studi Kasus TB. Santia Jaya Karawang - Anggita Wulandari; Suroso; Flora Patricia Anggela (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to examine how situational leadership styles and job satisfaction impact employee performance at TB. Santia Jaya Karawang. The research method employed a quantitative approach involving 60 employees from TB. Santia Jaya Karawang as the study sample, utilizing a saturated sampling technique. Data analysis was conducted using multiple linear regression with F and t-tests, with a significance level of 5%. The research findings indicate that situational leadership style (X1) significantly influences employee performance at TB. Santia Jaya Karawang, with a t-table value (2.735 > 2.002) or t-statistic > t-table. Additionally, it was revealed that job satisfaction (X2) partially affects employee performance at TB. Santia Jaya Karawang, with a t-table value (3.956 > 2.002) or t-statistic > t-table. Overall, situational leadership styles and job satisfaction collectively impact employee performance (Y), as indicated by an F-value of 21.509 > 3.16. Therefore, the combined effect of situational leadership styles and job satisfaction on employee performance at TB. Santia Jaya Karawang is 43%, while the remaining 57% is influenced by other factors not examined in this study.